Chemical Composition and mineral bioavailability of Tetrapleura tetraptera (Schumach & Thonn.) Taub. Fruit Pulp Consumed as Spice in South-eastern Côte d’Ivoire. - N’zebo Jean-Michel N’zebo; Amedée Pascal Ahi; Kouakou Martin Dje; Aka Faustin Kabran; Lucien Patrice Kouamé (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to evaluate the chemical composition and mineral bioavailability of T. tetraptera fruit pulp, an aromatic wild edible plant, using standard methods. The pulp were extracted from mature dried fruits obtained from plants at Awabo (5°30’14.2”N and 4°01’30.6”W) and Loviguié villages (5°48’24.5’’N and 4°20’15.8”W), all in south-eastern Côte d’Ivoire. The results of chemical analysis revealed that T. tetraptera fruit pulp contains carbohydrates (63.73±0.51%), crude protein (7.01±0.66%), crude fat (1.18±0.01%), ash (5.38±0.18%), fibre (11.78±0.02%), moisture (40.52±0.18%) and an energy value of 254.74±0.15 kcal/100g. Besides, the results showed a relative high amount of vitamin A (2.11±0.02%) and vitamin B9 (261.78±0.01 µg/100g) while vitamin E, B1 and B2 in trace concentration. Otherwise, the phytochemical analysis (mg/100g) based on dry weight revealed an appreciable amount of total phenol (2407.10±8.36), flavonoids (14.29±0.56), tannins (55.11±0.44), catechin (392.93±1.01) and also carotenoids (108.19±7.42 µg/100g). Organic acids profile (mg/100mL) showed citric acid (175.06±0.02) and salicylic acid (109.85±0.01) as major organic acids. Mineral composition (mg/100g) on dry weight basis revealed that potassium (1303.67±0.58) is the most abundant followed by phosphorus (303.33±5.77), calcium (187.33±0.58) and magnesium (141.33±0.57). Furthermore, the Phytates:Zn, Phytates:Ca, Oxalates:Ca and Phytates*Ca:Zn molar ratios recorded were all below than recommended threshold values, implying a bioavailability of zinc and calcium. These data indicate that the pulp of this fruit could be a good source of ingredient for both medicine and food industries in production.